Credit Advisers, Consumer Credit and Equitable Fiduciary Obligations. (March 2019) - Degeling, Simone; Hudson, Jessica
Consumers use financial intermediaries such as brokers and other credit advisers to navigate complex financial markets and to provide guidance on credit products. In 2017 ASIC reported that '[b]rokers … are responsible for arranging … half of all home loans in Australia' (Australian Securities & Investments Commission, Report 516: Review of Mortgage Broker Remuneration (2017) 8 [18]). The National Consumer Credit Protection Act 2009 (Cth) ('Credit Regime') regulates the conduct of such advisers including requiring disclosure of fees and some commissions. The Credit Regime also permits conflicts between the interest of the adviser and the client, provided that the adviser has in place 'adequate arrangements to ensure … [that the client is] … not disadvantaged by any conflict of interest' and that the conflict does not breach the adviser's obligation to act 'efficiently, honestly and fairly'. This article demonstrates that equitable fiduciary obligations also operate to regulate the conduct of the adviser in his or her dealings with the client. Such conflict and other conduct may breach any equitable fiduciary obligation thus exposing the adviser to equitable remedies. Equitable fiduciary obligations may thus be an as yet under-exploited avenue of protection for consumers and a concomitant zone of compliance risk for those subject to the Credit Regime.